Study on the Equivalence of Penetration Overloading for Projectile-Borne Components in Nonproportional Penetrators. (25th February 2022) - Yan, Amin; Pi, Aiguo; Yang, He; Huang, Fenglei; Wang, Xiaofeng
Abstract : The reliability assessment of the projectile-borne components in a high-speed penetrator is an important issue in the penetration field. In this study, a scaling model embedded with a deceleration measurement device was used to investigate the overloading situation due to the high cost of the prototype test. The projectile could be scaled, while the deceleration measurement device needs to maintain full scale. Thus, a nonproportional scaling design is proposed to represent the rigid-body deceleration of the prototype projectile. This study, considering the mass of the deceleration measurement device, lays out the design criteria of the scaling model and carries out rigid-body deceleration similarity verification tests of the prototype and the scaling model. In addition, the rigid-body deceleration similarity was examined through model predictions and numerical simulation. These results show that the rigid-body deceleration of the nonproportional scaling model is generally in agreement with that of the prototype for penetrating the semi-infinite concrete target. The deviations of rigid-body deceleration magnitude and duration are 6.76% and −12.1%, respectively. This makes it reasonable and feasible to investigate the overloading situation of prototype projectile through a nonproportional scaling model.